Навʼя-ньяя: з історії становлення логічної школи в Індії - Пхиденко, Станіслав; Pkhydenco, Stanislav (Східноєвропейський національний університет імені Лесі Українки, 2014)
Уперше у вітчизняній науковій літературі здійснено спробу з’ясувати історію становлення логічної школи навʼя-ньяя, у перекладі зі санскриту – нова ньяя, систематизувати погляди зарубіжних індологів на походження та зміст нової, некласичної логіки, запропоновано загальну оцінку значення малодослідженої реформи логічних знань середньовічних наяїків. For the first time in the national scholarly literature an attempt is made to investigate the history of the formation of the Navya-Nyaya (New Nyaya), an Indian logic school of the 14–17 centuies. Due to the efforts of Gangesha, the founder of this doctrine, and a number of his followers (Vardhamana, Radhunatha, Mathuranatha and others) the classicfl school of Nuaya wos gualitatively modified. As a result, the world’s first speciment of a symbolic logic (notably, the logic of relations) was created. The article contains a systematized overview of the approacbes of foreign indologists to the issue of origin and contents of the new nonclassical science of logic. A general assessment of the scantily-studied reform of the logic knowledge of the late-medieval Nyaya proponents is performed.
The navya-nyaya logical doctrine of India: History of the Making
Keywords: ньяя; навʼя-ньяя; синкретична школа; символічна логіка ньяї; анумана; в’япті; специфікація; проникання; nyaya; navya-nyaya; syncretic school; symbolic logic of nyaya; anumana; vyapty; specisipation; penetration